The experience of violence against women and girls in Southwest, Nigeria - Ibekwe, Ogechukwu C.; Kareem, Abiodun J.; Akpoti, Okehi O.; Ogunromo, Ayodele Y.; Oluwatuyi, Korede O.; Ejiyooye, Toluwalope (International Journal Of Community Medicine And Public Health, 2022)
Background: Violence against women and girls is a universal malaise that involved all aspect of life irrespective of culture, status, religion, or age. Despite efforts in curbing the menace, women’s rights are still threatened. This study aimed to assess the experience of violence against women and girls in southwest, Nigeria Methods: A descriptive cross-sectional design was used for this study. Quantitative and qualitative data were collected using a semi-structured interviewer-administered questionnaire and a key informant interview guide from 413 women/girls with age >18 years. The data were analyzed using descriptive and inferential statistics. P value <0.05 was considered significant. Results: Physical violence 338 (81.8%) was the most common type of violence known while emotional violence 57 (98.1%) was the most common violence experienced. The prevalence of violence against women and girls was 15.5%. The factors associated with violence against women and girls were age (χ2=13.92; p=0.008) and marital status (χ2=67.62; p=0.001).Some of the causes of violence against women and girls were the weakness of the women and misunderstanding between the couples while the solution to the menace were the education of the women, and appropriate punishment for the perpetrators which should be enforced. Conclusions: Violence against women and girls is a malaise that can be curbed if appropriate measures are jointly taken by all and such imbibed into our culture.